Influence of light-polymerizing units and zirconia on the physical, chemical and biological properties of self-adhesive resin cements - Siriwong Wongsirisuwan; Narin Intarak; Sasiprapa Prommanee; Noppadol Sa-; Sunporn Namano; Dusit Nantanapiboon; Thantrira Porntaveetus (BMC, 2024)
Abstract Background Self-adhesive resin cements (SARCs) are widely used for fixed prostheses, but incomplete cleaning near the gingival margin can cause inflammation. However, the factors influencing cement properties and the biological response of gingival fibroblasts to cement eluates are not well understood. This study examines the impact of two light-polymerizing units (LPUs) on the physical and chemical properties of two SARCs under simulated clinical conditions, as well as the subsequent response of human gingival fibroblasts (hGFs) to these eluates. Methods Dental cement discs of SARCs were polymerized using Kerr DemiPlus and 3 M Elipar DeepCure-S LED LPUs with or without a 2-mm thick zirconia screen. Physical properties (microhardness, surface roughness, residual monomers) were evaluated. hGFs' cell viability, wound healing potency, and gene expression were assessed. Results Both Maxcem and RelyX exhibited reduced microhardness and increased surface roughness when polymerized through zirconia or with DemiPlus LPU. Higher residual monomers (HEMA and GDMA in Maxcem; TEGDMA in RelyX) concentration was observed with DemiPlus and zirconia polymerization. Maxcem polymerized with DemiPlus exhibited lower cell viability, impaired healing, and altered gene expression in hGFs compared to those polymerized with Elipar LPU. Gene expression changes included downregulated NRF2 and HO-1 and upregulated CCR-3. Conclusions Light-polymerizing Maxcem through zirconia with DemiPlus LPU compromised SARCs' properties, leading to higher residual monomers and negatively impacting hGFs' viability, healing, and gene expression. Careful material selection and polymerization techniques are crucial to minimize adverse effects on surrounding tissues. Clinical significance Clinicians should exercise caution when using LPUs and SARCs, especially when polymerizing through zirconia. This will help optimize the physical and chemical properties of SARCs and minimize potential adverse effects on the surrounding gingival soft tissues.